The moderating effect of program context on the relationship between program managers' leadership competences and program success. Issue 1 (January 2018) - Shao, Jingting
Abstract: We investigated the moderating effect of program context on the relationship between leadership competences of program managers and program success. Leadership competence was measured as the combination of intellectual competence (IQ), managerial competence (MQ) and emotional competence (EQ). A worldwide cross-sectional survey using the Leadership Dimensions Questionnaire (LDQ) and a program context and success questionnaire yielded 79 responses. Moderated hierarchical regression analyses (MHRA) were used to test the moderating effect of program context, which is characterized by organizational fit, program flexibility, organizational stability and resource availability. Results showed that program context positively moderates the relationships between program managers' IQ respective MQ with program success. However, the relationship between EQ and program success is lowered to insignificance in the presence of context. Managerial and theoretical implications are discussed. Highlights: The relationship of program manager's IQ and program success is moderated by program context. The relationship of program manager's MQ and program success is moderated by program context. The relationship of program manager's EQ and program success is moderated by program context. Program manager's IQ and MQ play a more direct role in achieving program success compared with EQ. A theoretic model "leadership competence based theory of program success" was developed.